2010
DOI: 10.1186/1471-2148-10-91
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of divergence time between two sibling species of the Anopheles (Kerteszia) cruziicomplex using a multilocus approach

Abstract: BackgroundAnopheles cruzii is the primary human Plasmodium vector in southern and southeastern Brazil. The distribution of this mosquito follows the coast of the Brazilian Atlantic Forest. Previous studies indicated that An. cruzii is a complex of cryptic species.ResultsA multilocus approach using six loci, three circadian clock genes and three encoding ribosomal proteins, was implemented to investigate in more detail the genetic differentiation between the An. cruzii populations from Santa Catarina (southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…Figure 3 shows the posterior probability distributions for each of the three parameters estimated using the IM program. The results suggested that the two species have not exchanged migrants since their separation and that they possibly diverged between 1.1 and 3.6 million years ago (Rona et al, 2010a). In fact, the divergence time between the southern and northeastern species fall within the Pleistocene, a period of intense climatic changes (Cantolla, 2003;Ravelo et al, 2004).…”
Section: Molecular Markers and The Genetic Differentiation Among Brazmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 shows the posterior probability distributions for each of the three parameters estimated using the IM program. The results suggested that the two species have not exchanged migrants since their separation and that they possibly diverged between 1.1 and 3.6 million years ago (Rona et al, 2010a). In fact, the divergence time between the southern and northeastern species fall within the Pleistocene, a period of intense climatic changes (Cantolla, 2003;Ravelo et al, 2004).…”
Section: Molecular Markers and The Genetic Differentiation Among Brazmentioning
confidence: 99%
“…cruzii, a multilocus analysis was carried out comparing Itaparica to Florianópolis (Rona et al, 2010a). The aim of this study was to determine if there is still gene flow between the two sibling species and to estimate their divergence time.…”
Section: Molecular Markers and The Genetic Differentiation Among Brazmentioning
confidence: 99%
See 2 more Smart Citations
“…O gene COI se mostrou extremamente polimórfico para a espécie Anopheles cruzii e nota-se uma estruturação populacional quando comparados morro e planície. Devido a sua importância como vetor de Plasmodium, o status taxonômico dessa espécie tem sido investigado por vários estudos recentes (Ramirez, Dessen, 2000a, b;Rona et al, 2009Rona et al, , 2010a. Para os autores, as diferenças genéticas e cromossômicas encontradas podem indicar o início de uma especiação dentro de An.…”
Section: Considerações Finaisunclassified